Anthroponyms in the Microtoponyms of the Aleksinac Area - Stefanović, Dušan R. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
This paper examines anthroponyms (male and female personal names, male and female hypocoristics, male nicknames, surnames, ethnics, and ethnonyms) involved in the formation of microtoponyms in the Aleksinac region. The primary focus is on structural analysis, complemented by semantic observations on other anthroponymic categories where relevant. The analyzed material reveals the extensive presence of anthroponyms in the local microtoponymy, making this study a logical continuation of our previous onomastic research on the Aleksinac area.